PENGARUH PERIKLANAN TELEVISI TERHADAP CITRA MEREK PRODUKKECAP ABC BLACK GOLDDI SURABAYA SELATAN - BASHORY ALWY, MOHAMAD (Jurnal Ilmu Manajemen (JIM), 2013)
This study uses the variable advertising trough mediatelevision (X) and brand image (Y). The population in this study iscunsomers who have seen the advertising ABC Black Gold soy souceproduct twice and they age 16 until 65 years old in the area of southsurabaya. Sampling tecniques used in this study was non-probabilitysampling method, which is using purposive sampling with the numberof 140 respondents. The data used are primary and secondary databy distributing on naires and interview instruments processing thedata obtained by using simple regression. Based on test results usingsimple regression analyzed it can be concluded that the advertisingfactor positive and significant impact on brand image.Keywords: television advertising and brand image.